The Effect of Flipped Classroom Method in Enhancing Vocational Students’ Speaking Skills in the Merdeka Curriculum - Yosy Siftia; Ferri Susanto; Anita (Fakultas Sastra - Universitas Muslim Indonesia, 2026)
This study was initiated by the low speaking skills of vocational school students, particularly at SMK Negeri 5 Seluma, which was caused by limited practice time in class and low active participation in English learning. This study aimed to investigate whether the implementation of the Flipped Classroom method has a significant effect on enhancing tenth-grade students' speaking skills within the Merdeka Curriculum framework at SMK Negeri 5 Seluma. The research design employed was a quantitative approach with a Quasi-Experimental design. The research population involved the tenth-grade students, selected through a purposive sampling technique, where Class X.TKJ (24 students) was designated as the experimental group taught using the Flipped Classroom method, and Class X.TBSM (19 students) served as the control group taught using the conventional method. Data were gathered through speaking oral tests via pre-test and post-test assessments measuring accuracy, fluency, and comprehension. The results revealed that the mean post-test score of the experimental group reached 79.5 (with scores rising from a minimum of 33 to a maximum of 100), while the control group only achieved a mean score of 46.52. The statistical analysis using the ANCOVA test via SPSS 25 yielded an F_observed value of 46.092, which was higher than the F_table value (4.00). Furthermore, the Partial Eta Squared value was 0.529, indicating that the Flipped Classroom method contributed 52.9% to the improvement of students' speaking performance. Based on these findings, it can be concluded that the Flipped Classroom method has a significant and effective impact on enhancing vocational students' English speaking skills at SMK Negeri 5 Seluma